Commonly Used Instruments and Procedures in O&G”. - Soe, Lwin; Tin Moe, Nwe (University of Malaysia Sarawak, 2022)
The book as a user-friendly handy and is mostly illustrated for the reader to understand the commonly used instruments and procedures in the field of basic Obstetrics and Gynaecology.